(untitled) (Journal of Computational Mathematics, 1990)
The Drazin inverse of a lower Hessenberg matrix is considered. If A is a singular lower Hessenberg matrix and a_i,i+1= eq 0,i=1,2,…,n-1, then A^D can be given, and expressed explicitly by elements of A. The structure of the Drazin inverse of a lower Hessenberg matrix is also studied.